Semangat Belajar PAI dengan Metode Bermain Peran (Role Playing) di SMKN 1 Setu Kabupaten Bekasi - alfiani, Nur Rachma Nisa Alfiani; Siti Asiah (LP3M Universitas Putra Bangsa, 2023)
Community Service is done to find out that 1) Whether the role play method can increase students' enthusiasm for learning, 2) Whether the role play method can be used in Islamic Religious Education subjects, 3) How the learning outcomes obtained if using the role play method. The type of research carried out is qualitative descriptive with samples taken are students / students of class X. The data was obtained through teaching activities and accompanying grade X students of SMKN 1 Setu. The results showed that role-playing methods can improve student enthusiasm and learning outcomes. This method has the advantage of giving the impression of learning that is fun and not monotonous, besides that the material delivered through role play will be much more durable remembered by students.